2000
DOI: 10.1074/jbc.m001299200
|View full text |Cite
|
Sign up to set email alerts
|

Arg-274 and Leu-277 of the γ-Aminobutyric Acid Type A Receptor α2 Subunit Define Agonist Efficacy and Potency

Abstract: Alanine-scanning mutagenesis and the whole cell voltage clamp technique were used to investigate the function of the extracellular loop between the second and third transmembrane domains (TM2-TM3) of the ␥-aminobutyric acid type A receptor (GABA A -R). A conserved arginine residue in the TM2-TM3 loop of the GABA A -R ␣ 2 subunit was mutated to alanine, and the mutant ␣ 2 (R274A) was co-expressed with wild-type ␤ 1 and ␥ 2S subunits in human embryonic kidney (HEK) 293 cells. The GABA EC 50 was increased by abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 40 publications
6
42
0
Order By: Relevance
“…Furthermore, we investigated the role of other basic residues located in TM2-3L of the ␤ 2 subunit (Arg 269 and Lys 279 ) and found that only the basic residue at position 274 is sensitive to a charge reversal mutation, suggesting that it is uniquely involved in electrostatic interactions important for receptor activation. This study also confirms the importance of TM2-3L of the GABA A -R ␤ 2 subunit in receptor activation, as previously reported for the ␣ 1 , ␣ 2 , ␤ 2 , and ␤ 3 subunits (12,14,18,25). An interesting difference between the ␣ 1 and ␤ 2 subunits was observed here because ␤ 2 (L272A) failed to alter receptor function, whereas the ␣ 1 ortholog (L277A) reduces GABA sensitivity dramatically (EC 50 ϭ 278 M) (26).…”
Section: Characterization Of Mutations In Loops 2 and 7 Of Thesupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, we investigated the role of other basic residues located in TM2-3L of the ␤ 2 subunit (Arg 269 and Lys 279 ) and found that only the basic residue at position 274 is sensitive to a charge reversal mutation, suggesting that it is uniquely involved in electrostatic interactions important for receptor activation. This study also confirms the importance of TM2-3L of the GABA A -R ␤ 2 subunit in receptor activation, as previously reported for the ␣ 1 , ␣ 2 , ␤ 2 , and ␤ 3 subunits (12,14,18,25). An interesting difference between the ␣ 1 and ␤ 2 subunits was observed here because ␤ 2 (L272A) failed to alter receptor function, whereas the ␣ 1 ortholog (L277A) reduces GABA sensitivity dramatically (EC 50 ϭ 278 M) (26).…”
Section: Characterization Of Mutations In Loops 2 and 7 Of Thesupporting
confidence: 75%
“…Previous reports have suggested that TM2-3L of the GABA A -R ␣ subunit is involved in receptor activation (12,18). To determine whether this domain in the GABA A -R ␤ 2 subunit plays a similar role, we created point mutations R269A, R269D, L272A, K274D, and K279D at positions corresponding to mutations in the GABA A -R ␣ subunit that are important for receptor function (12,18). The mutant receptors were then characterized by determining GABA concentration-response curves.…”
Section: Characterization Of Mutations In the Tm2-tm3mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these difficulties, techniques have been developed that can potentially identify binding or gating changes using EC 50 and peak current measurements. For example, the relative efficacy of a partial agonist has been used as an internal control for receptor expression, and changes in relative efficacy have thus been interpreted as being caused by gating changes (Maksay et al, 2000;O'Shea and Harrison, 2000;Wagner and Czajkowski, 2001). In contrast, evidence for binding changes has included: (1) a change in the potency of GABA that is not accompanied by a change in the potency of a modulator that opens the channel but does not bind at the GABA-binding site, and (2) large changes in GABA potency in the absence of large changes in maximal cur- rent (Amin and Weiss, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that mutations in this region disrupt activation in nACh, 5-HT 3 , GABA and Gly receptors (Campos-Caro et al 1996 ;Deane & Lummis, 2001 ;Grosman et al 2000aGrosman et al , 2000bKusama et al 1994 ;Lewis et al 1998 ;Lynch et al 1997 ;O'Shea & Harrison, 2000 ;Rajendra et al 1995 ;Rovira et al 1998Rovira et al , 1999Saul et al 1999 ;Sigel et al 1999). The structure of this loop has been examined by a range of techniques, including NMR and electron microscopy, and the data suggest that there are differences between cation-and anion-selective receptors.…”
Section: The M2-m3 Loopmentioning
confidence: 99%